Effect of electron-magnon coupling on the electronic spectrum of weakly doped high-Tc compounds - Ivanov, M. A.; Loktev, V. M.; Pogorelov, Yu. G. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1998)
A theoretic analysis of magnon-induced damping Г of quasiparticle states in the normal phase of doped copper-oxide high-Tc materials is developed, based on a microscopic model which accounts for the specific 2D structure of their electron and magnon spectra. Among the obtained energy and temperature dependences of Г in different regimes, the most peculiar is the anomalously early onset of linear temperature dependence ГµT with a doping-independent coefficient.